2016
DOI: 10.1038/srep32515
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Angle Insensitivity of Ultrathin Planar Optical Absorbers for Broadband Solar Energy Harvesting

Abstract: Two challenging problems still remain for optical absorbers consisting of an ultrathin planar semiconductor film on top of an opaque metallic substrate. One is the angle-insensitive mechanism and the other is the system design needed for broadband solar energy harvesting. Here, first we theoretically demonstrates that the high refractive index, instead of the ultrathin feature as reported in previous studies, is the physical origin of the angle insensitivity for ultrathin planar optical absorbers. They exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…As shown in Fig. 1c, this matching is obtained in a range of 600-700 nm for Ge (in agreement with previous studies [85][86][87]), while the matching is satisfied in wavelength values below 500 nm for PVSK and Fe 2 O 3 [82]. Increasing D S to 25 nm, Ge loses its matching, while Fe 2 O 3 absorption upper edge experiences a red shift (see Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Fig. 1c, this matching is obtained in a range of 600-700 nm for Ge (in agreement with previous studies [85][86][87]), while the matching is satisfied in wavelength values below 500 nm for PVSK and Fe 2 O 3 [82]. Increasing D S to 25 nm, Ge loses its matching, while Fe 2 O 3 absorption upper edge experiences a red shift (see Fig.…”
Section: Resultssupporting
confidence: 91%
“…The strong interface effects, induced by a bottom mirror, can provide light nearly perfect absorption in this design. In this configuration, the right choice of semiconductor geometries can significantly enhance the light-matter interaction [82][83][84][85][86][87]. However, this configuration can enhance light absorption to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…Later, a proof‐of‐concept device has been made to reveal the potential of ultrathin transition metal dichalcogenides (TMDs) for energy conversion applications . A 22 nm thick Fe 2 O 3 on Ag mirror has also been shown to have strong light absorption at λ < 450 nm . Similar optical responses have been realized for another type of metals and semiconductors .…”
Section: Light Trapping Schemesmentioning
confidence: 88%
“…This strong, light-matter interaction can lead to exceeding the Yablonovitch limit [48]. Later studies demonstrated many different MS configurations that achieve stronger and broader light absorption [49]- [51]. This is of great interest in photoelectronic applications, which confine light in dimensions much smaller than the carrier's diffusion length.…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 99%